Video-based agricultural extension: Analysis of a pilot project in Ethiopia - Bernard, Tanguy; Makhija, Simrin; Orkin, Kate; Taffesse, Alemayehu Seyoum; Spielman, David J. (International Food Policy Research Institute, 2016)
Since 2014, Digital Green and the Government of Ethiopia have been piloting a project to introduce a community-centric video approach to agricultural extension provision.1 Digital Green’s approach has the potential to transform extension in Ethiopia via a fairly simple impact pathway. By providing a cost-effective ap-proach to information dissemination, video-based extension can in-crease the adoption rate of productivity-enhancing agricultural technologies and practices by smallholder farmers, including in-creased adoption by women. The Digital Green approach could also improve data collection and analysis. This note, based on a more detailed project report,2 summarizes findings and recom-mendations that point the way to expanded use of video-based ag-ricultural extension.